Antacid therapy for gastroesophageal reflux in preterm infants: a systematic review - Jon Dorling; Elda Dermyshi; Charley Mackie; Phoebe Kigozi; Bernard Schoonakker (BMJ Publishing Group, 2018)
Background Gastro-oesophageal reflux is prevalent in preterm infants. Despite widespread use in clinical practice, there is still much controversy over the efficacy and safety of drug interventions, particularly antacid therapy.Objective To systematically review the effects of antacid therapy on preterm infants with symptoms of gastro-oesophageal reflux, and to assess the safety of these interventions.Methods We carried out an electronic search of the Cochrane central register of controlled trials (CENTRAL, The Cochrane Library), MEDLINE (1966-present), EMBASE (1980-present) and CINAHL (1982-present) as well as other online sources. Participants were preterm infants (<37 weeks gestation) with gastro-oesophageal reflux disease who were receiving care on a neonatal unit. We assessed the effects of histamine-2 receptor antagonists, proton pump inhibitors and alginates against placebo, primarily to see if they reduced the symptoms of reflux.Results Six studies were included in this review. Meta-analysis could not be carried out due to a lack of studies assessing the same intervention with the same outcomes. Omeprazole therapy significantly reduced the oesophageal acid exposure percentage time with pH<4 (p<0.01) and sodium alginate significantly decreased gastro-oesophageal reflux episodes (p=0.024). Metoclopramide and ranitidine showed a significant increase in gastro-oesophageal reflux disease symptoms versus placebo (p<0.04). No significant results were found for the use of esomeprazole or lansoprazole versus placebo.Conclusions There is insufficient evidence available to conclude whether antacid therapy is effective or safe when treating gastro-oesophageal reflux disease in preterm infants. Further research is needed into this topic and caution should be taken when administering antacids to preterm infants.Trial registration number CRD42017078778